Accurate Evaluation of Hepatocyte Metabolisms on a Noble Oxygen-Permeable Material With Low Sorption Characteristics - Nishikawa, Masaki; Ito, Hiroyasu; Tokito, Fumiya; Hirono, Keita; Inamura, Kousuke; Scheidecker, Benedikt; Danoy, Mathieu; Kawanishi, Takumi; Arakawa, Hirohsi; Kato, Yukio; Esashika, Katsuhiro; Miyasako, Hiroshi; et al. (Frontiers in Toxicology, 2022)
In the pharmaceutical industry, primary cultured hepatocytes are a standard tool used to assess hepatic metabolisms and toxicity in vitro. Drawbacks, however, include their functional deterioration upon isolation mostly due to the lack of a physiological environment. Polydimethylsiloxane (PDMS) has been reported to improve function of isolated hepatocytes by its high oxygen permeability and when used as a material of microphysiological systems (MPS). However, its high chemical sorption property has impeded its practical use in drug development. In this study, we evaluated a new culture material, 4-polymethyl-1-pentene polymer (PMP), in comparison with PDMS and conventional tissue culture polystyrene (TCPS). First, we confirmed the high oxygen permeability and low sorption of PMP, and these properties were comparable with PDMS and TCPS, respectively. Moreover, using primary rat hepatocytes, we demonstrated maintained high levels of liver function at least for one week on PMP, with its low chemical sorption and high oxygen permeability being key factors in both revealing the potential of primary cultured hepatocytes and in performing accurate evaluation of hepatic metabolisms. Taken together, we conclude that PMP is a superior alternative to both PDMS and TCPS, and a promising material for a variety of drug testing systems.